Interval breast cancer is associated with interferon immune response. (February 2022) - Ugalde-Morales, Emilio; Grassmann, Felix; Humphreys, Keith; Li, Jingmei; Eriksson, Mikael; Tobin, Nicholas P.; Lindström, Linda S.; Vallon-Christersson, Johan; Borg, Åke; Hall, Per; Czene, Kamila
Abstract: Background: The aggressive nature of breast cancers detected between planned mammographic screens, so-called interval cancers, remains elusive. Here, we aim to characterise underlying molecular features of interval cancer. Methods: From 672 patients with invasive breast cancer, we analysed gene expression differences between 90 'true' interval cancer cases (i.e. women with low-dense breasts defined as per cent mammographic density <25%) and 310 screen-detected tumours while accounting for PAM50 subtypes and thus overall tumour aggressiveness. We computed an interval cancer gene expression profile (IC-Gx) in a total of 2270 breast tumours (regardless of interval cancer status) and tested for association with expression-based immune subtypes in breast cancer. In addition, we investigated the contribution of inherited and somatic genetic variants in distinct features of interval cancer. Results: We identified 8331 genes nominally associated with interval cancer ( P -value < 0.05, fold-change > 1.5). Gene set enrichment analysis showed immune-related pathways as key processes altered in interval cancer. Our IC-Gx, based on 47 genes with the strongest associations (false discovery rate < 0.05), was found to be associated mainly with immune subtypes involving interferon response. We isolated an interaction network of interval cancer and interferon genes for which a significant load of somatic and germline variants in class I interferon genes was observed. Conclusion: We identified novel molecular features of interval breast cancer highlighting interferon pathways as a potential target for prevention or treatment. Highlights: Identification of molecular features of interval breast cancer independent of PAM50. Interval cancer gene expression linked to upregulation of immune response pathways. Immune subtypes related to interferon signalling are associated with interval cancer. Mutation load in interferon and related genes is associated with interval cancer. Results suggest a novel role of interferon signalling in interval breast cancer.